2017
DOI: 10.1371/journal.pone.0186724
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of severe anemia among laboring mothers in Mekelle city public hospitals, Tigray region, Ethiopia

Abstract: IntroductionAnemia is a global public health problem that has affected a significant number of pregnant mothers worldwide. The World Health Organization has estimated the prevalence of anemia in pregnant women at 18% and 56% in developed and developing countries, respectively. This study aimed to identify factors associated with severe anemia among laboring women in Mekelle city public hospitals, Tigray, Ethiopia.MethodsThis unmatched case–control study involved 264 (88 = cases and 176 = controls) pregnant wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 12 publications
7
14
0
Order By: Relevance
“…Those pregnant with a low diversity diet were found with higher odds of developing anemia compared with the high dietary diversity. The result is consistent with the study of Ethiopia (35), Mekelle town (36) and also with the study in nine regional states of Ethiopia (37). The previous study among women of the Terai belt of Nepal also explored diets of women have less diversity and inadequacy in nutrition (38).…”
Section: Discussionsupporting
confidence: 92%
“…Those pregnant with a low diversity diet were found with higher odds of developing anemia compared with the high dietary diversity. The result is consistent with the study of Ethiopia (35), Mekelle town (36) and also with the study in nine regional states of Ethiopia (37). The previous study among women of the Terai belt of Nepal also explored diets of women have less diversity and inadequacy in nutrition (38).…”
Section: Discussionsupporting
confidence: 92%
“…Although statistically older, several authors [5][6][7][8][9][10] found an age around thirty with a peak between 25 and 34 years, making anemia in pregnancy a pathology of the young adult. However, Alemu [11] in Ethiopia, reports a prevalence of the age group of 40 to 44 years (30%) with a risk three times higher of anemia (OR = 3.43 [1.04-11.28]).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the influence of certain cultural considerations such as the marriage of adolescent girls, culinary habits were mentioned [5,6,8,9,.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations